2022
DOI: 10.3389/fcvm.2022.1010693
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of sodium glucose co-transporter 2 (SGLT2) inhibitors: A brief summary

Abstract: A new therapeutic class of oral agents firstly used for the treatment of type 2 diabetes mellitus is represented by gliflozines or sodium-glucose co-transporter 2 (SGLT2) inhibitors. SGLT2 inhibitors might be effective alone or in combination with any other drugs. This therapeutic class currently includes five agents: canagliflozin, dapagliflozin, empagliflozin, ertugliflozin, and sotagliflozin. SGLT2 inhibitors prevent the renal reabsorption of filtered glucose and sodium by blocking the SGLT2 co-transporters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 64 publications
0
16
0
4
Order By: Relevance
“…Regarding selection of prescribed drugs, special focus was put on newly recommended cardio- and renal-protective antidiabetic drugs, glucagon-like peptide-1 receptor agonist (GLP1ra), and sodium-glucose cotransporter-2 inhibitors (SGLT2inh), for their potential anti-inflammatory effects [ 41 , 45 ]. An old-fashioned first-line antidiabetic drug, metformin, and statins are widely prescribed to diabetic patients, and for both drugs, besides their metabolic effects, direct involvement in IL-17A signaling has been identified [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding selection of prescribed drugs, special focus was put on newly recommended cardio- and renal-protective antidiabetic drugs, glucagon-like peptide-1 receptor agonist (GLP1ra), and sodium-glucose cotransporter-2 inhibitors (SGLT2inh), for their potential anti-inflammatory effects [ 41 , 45 ]. An old-fashioned first-line antidiabetic drug, metformin, and statins are widely prescribed to diabetic patients, and for both drugs, besides their metabolic effects, direct involvement in IL-17A signaling has been identified [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…SGLT-2i are comparable in efficacy to GLP-1 RA in reducing hepatic decompensations[ 117 ]. A study found that the use of SGLT-2i in cirrhotic patients prevents worsening liver function and hepatic fibrosis[ 129 ]. There are also case reports where the addition of SGLT-2i controlled ascites, hydrothorax, and peripheral edema[ 130 ].…”
Section: Treatmentmentioning
confidence: 99%
“…There were initial concerns about the increased risk of hypoglycemia and urinary tract infections, but a significant increase in these 2 adverse events has not been reported across several trials. 22 23) SGLT-2 do increase the risk of genital mycotic infections, but the absolute risk is low and considering the benefit with these drugs and the easily treatable nature of genital mycotic infections, the recommendations are to continue treatment, unless these infections are recurrent. 1 11) Fournier’s gangrene, defined as necrotizing fasciitis of perineal soft issues, has also been reported as a rare adverse effect 24) and has been identified as a safety warning.…”
Section: Safety Eventsmentioning
confidence: 99%